First Report of Aspergillus niger Causing Root Rot of Peanut in China - Xu, M L (Plant disease, 2015)
Peanut (Arachis hypogaea) is one of the most important oil crops and food legumes worldwide. China sows approximately 3.5 million hectares each year and produces 40% of the world's peanuts. Fungal diseases are among the main biotic stresses affecting peanut production. Root rot is a serious disease caused by several fungi. Pythium spp., Fusarium spp., and Rhizopus spp. are some of the root rot fungi that have been reported in China. In 2012 and 2013, root rot symptoms were observed in several fields in Laixi District, Qingdao City, Shandong Province, China. The first symptoms appeared in July. Initial symptoms of the disease were brown spots on the stem base and root. Affected plants were stunted, with leaf chlorosis, reduced growth, or sudden wilting. As disease progressed, the infected tissues showed brown discoloration and rot, and abundant dark brown and black powdery spores were visible on the surfaces of affected parts. Eventually, affected plants collapsed and died. To isolate the causal organism, roots and stems were cut into sections, which were surface-disinfected with 70% ethanol solution (v/v) for 20 s, soaked in 0.1% mercuric chloride solution for 50 s, rinsed with sterilized water three times, dried, placed on Czapek's Dox agar supplemented with chloramphenicol (100 μg/ml), and incubated at 28°C for 7 days. Fungal colonies were white initially and then covered with a dense layer of dark brown or black conidial heads. The conidial head was radiate; vesicles were nearly spherical and covered with irregular metulae and phialides. Conidia were globose or subglobose (3.0 to 5.5 μm in diameter), dark brown to black, with rough cell walls. Total genomic DNA was extracted from mycelia using the EasyPure Genomic DNA Kit (TransGEN, Beijing, China). The rDNA-ITS region was amplified using PCR with the universal fungal primers ITS1 and ITS4 (2). The purified products were separately sequenced in both directions using the same primer pair. The sequences (GenBank Accession No. KJ848716) obtained were 99% similar to the ITS sequence of isolates of Aspergillus niger. This, together with the morphological characters (1) described above, suggested that the microorganism we had isolated was A. niger. Koch's postulates were completed in the laboratory by inoculating peanut. Thirty Huayu20 peanut seeds were placed in a 500-ml sterile pot with 300 g of autoclaved soil. Twenty days after seedling emergence, 15 peanut plants were wounded with a needle and inoculated with 5 ml of conidia suspension (106 ml-1). The same number of peanuts were similarly wounded and inoculated with 5 ml of sterile distilled water to serve as controls in the same pot. All peanuts were kept in a randomized complete block design at 30°C under a 12-h photoperiod. After 7 days, disease symptoms similar to those observed in the field appeared in all inoculated but not in non-inoculated peanuts. The tests were repeated three times in the greenhouse. Koch's postulates were satisfied after re-isolating the A. niger from inoculated peanuts using the method described above. To our knowledge, this is the first report of A. niger causing root rot in peanut in China. References: (1) M. A. Klich. Page 12 in: Identification of Common Aspergillus Species. Centraalbureau voor Schimmelcultures, Utrecht, The Netherlands, 2002. (2) T. J. White et al. Page 315 in: PCR Protocols: A Guide to Methods and Applications. Academic Press, San Diego, CA, 1990